CREATIVE STAFF AS A FACTOR OF THE ENTERPRISE’S SUCCESS - Nataliia Ivanova; Diana Kucherenko; Tetyana Kuznetsova; Alla Rasulova; Olha Salimon (Фінансово-кредитна діяльність: проблеми теорії та практики, 2022)
Changes in the economic, technological, social and demographic situation in recent years have caused a number of new phenomena at all levels of economic activity. These include increasing the availability of information and the speed of exchange; changes in the structure and nature of consumption of goods and services; increasing the rate of change in the economy and its discrete nature; increasing competition. At present, it is not enough for companies to provide quality products and services in order to be successful in their field, as the number of similar products and services on the market is growing every year. Therefore, the creation of unique products and making effective extraordinary creative decisions come to the fore. Analysis of the experience of the most successful companies revealed key factors in their success. This promotes the development of the creative abilities of staff; creating a highly productive work environment; involvement of the most talented and creative managers; providing processes, methods and funding to support creative initiatives. In other words, we are talking about the formation and development of creative staff. To confirm the impact of staff creativity on entrepreneurship, the authors analyzed global indices of creativity and entrepreneurship. The analysis allowed us to conclude that there is a significant link between creativity and entrepreneurship. Thus, it can be argued that creativity is an important component of successful entrepreneurship. This means that the more creative the company and its potential, ie the more the team is able to think creatively and create creative ideas, the more innovative products and services the team can provide, and the greater the success of the company. Research shows that Ukrainian companies employ people who have great intellectual potential, and who are able to generate creative ideas and turn them into innovations. However, there is a number of reasons why employees cannot realize this potential and convert creative ideas into innovation. These reasons include both objective and subjective. Objective reasons are the lack of funds and the weak mechanism for implementing new ideas in the activities of enterprises, low employment, the outflow of the most qualified personnel abroad. Subjective reasons include the following: the adherence of managers to management methods that were formed in a team economy; weak motivation of work behavior; fear of changing the usual way of working; unwillingness to make efforts for additional training. Thus, the issue of forming and stimulating the development of creative thinking of the staff of domestic enterprises and organizations is extremely important.